2010
DOI: 10.1080/13803391003596421
|View full text |Cite
|
Sign up to set email alerts
|

The validity of d prime as a working memory index: Results from the “Bergen n-back task”

Abstract: The n-back task is frequently used as an experimental paradigm in imaging studies of working memory. This study aimed to investigate whether the Bergen 2-back task is suitable for use in desktop assessment of patients with schizophrenia. Looking at the psychometric properties of the task, including the newly added measure of discriminability, d prime (d '), our analyses confirmed that the 2-back d ' is the preferred measure of working memory dysfunction in desktop assessment compared to the Digit Span Backward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
186
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(190 citation statements)
references
References 24 publications
4
186
0
Order By: Relevance
“…To test whether task-related changes in rCBF and FCS might relate to behavioral performance, we conducted a voxel-wise correlation analysis between the changes in rCBF or FCS and task performance, dprime, which is a measurement of hit rate and penalizing for the false alarm rate (23). As expected, we found that the behavioral performance positively correlated with working-memory task-related changes in FCS in the right inferior-parietal lobule (P corrected < 0.05), and task-related changes in rCBF in the left inferior-parietal lobule at the 3-back level (P corrected < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether task-related changes in rCBF and FCS might relate to behavioral performance, we conducted a voxel-wise correlation analysis between the changes in rCBF or FCS and task performance, dprime, which is a measurement of hit rate and penalizing for the false alarm rate (23). As expected, we found that the behavioral performance positively correlated with working-memory task-related changes in FCS in the right inferior-parietal lobule (P corrected < 0.05), and task-related changes in rCBF in the left inferior-parietal lobule at the 3-back level (P corrected < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity index d′ (Haatveit et al, 2010;Green and Swets, 1988) and reaction times were used to analyze the behavioral performance. D′ is calculated as the standardized probability of a hit minus the standardized probability of a false alarm: d′ = z(probability(hits)) − z(probability(false alarms)).…”
Section: Behavioral Analysesmentioning
confidence: 99%
“…In (Perry et al, 2001;Egeland et al, 2003;Haatveit et al, 2010). Additionally, it has been shown that different WM tests require varying amounts of executive function and research using factor analytic approach demonstrated that FDS and BDS tasks load together to form a factor separate from other tests with higher central executive WM demands, such as N-back task (Allen et al, 2010).…”
Section: Discussion Different Domains Of Wm With Respect To Psychosismentioning
confidence: 99%